2017
DOI: 10.20959/wjpr20178-9195
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Standardization of “Parada Marita and Vanaspati Jarita Marita Yashada Bhasma” – A Comparative Study

Abstract: Introduction: Yashada bhasma (Calx of Zinc) is a metallic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Bhasma Pariksha done at different stages of Puta (incineration setup) revealed that PMY fulfilled classical parameters of Bhasma after 7 th Puta, whereas JMY required 5 Puta for the same. [3] Ash value analysis showed that both samples have good solubility in HCl. Variations in the solid content and pH value of the media after Shodhana of Yashada depicts the transfer of certain impurities from the metal to the Shodhana media.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Bhasma Pariksha done at different stages of Puta (incineration setup) revealed that PMY fulfilled classical parameters of Bhasma after 7 th Puta, whereas JMY required 5 Puta for the same. [3] Ash value analysis showed that both samples have good solubility in HCl. Variations in the solid content and pH value of the media after Shodhana of Yashada depicts the transfer of certain impurities from the metal to the Shodhana media.…”
Section: Discussionmentioning
confidence: 97%
“…Parada Marita Yashada Bhasma (PMY) and Vanaspati Jarita Marita Yashada Bhasma (JMY) were prepared as per classical Ayurveda guidelines. [3] PMY sample was prepared by means of Pishti preparation with Parada (Mercury) and Gandhaka (sulfur) and JMY sample prepared with prior Jarana (roasting) with Apamarga Panchanga (whole plant of Achyranthes aspera Linn.). [4] Both were subjected to (puta) incineration in electric muffle furnace (EMF).…”
Section: Methods Of Preparation Of Test Drugsmentioning
confidence: 99%
“…[10] After this procedure, both samples were subjected to incineration in electric muffle furnace to prepare Bhasma . [11]…”
Section: Methodsmentioning
confidence: 99%